The fungal neurotoxin penitrem A induces the production of reactive oxygen species in human neutrophils at submicromolar concentrations. (1st December 2017) - Berntsen, H.F.; Bogen, I.L.; Wigestrand, M.B.; Fonnum, F.; Walaas, S.I.; Moldes-Anaya, A.
Graphical abstract: Highlights: The fungal metabolite penitrem A causes intoxication in animals and humans. Penitrem A induce ROS production in human neutrophils. The mechanism of ROS formation seems to involve an activation of several MAPK signalling pathways as well as an increase in intracellular calcium. Penitrem A-induced ROS production may partly explain the pathophysiology generated by penitrem A neuromycotoxicosis. Abstract: Penitrem A is a fungal neurotoxin that recurrently causes intoxication in animals, and occasionally also in humans. We have previously reported that penitrem A induced the production of reactive oxygen species (ROS) in rat cerebellar granule cells, opening for a new mechanism of action for the neurotoxin. The aim of this study was to examine the potential of penitrem A to induce ROS production in isolated human neutrophil granulocytes, and to study possible mechanisms involved. Penitrem A significantly increased the production of ROS in human neutrophils at concentrations as low as 0.25 μM (40% increase over basal levels), as measured with the DCF fluorescence assay. The EC50 determined for the production of ROS by penitrem A was 3.8 μM. The maximal increase in ROS production was approximately 330% over basal levels at a concentration of 12.5 μM. ROS formation was significantly inhibited by the antioxidant vitamin E (50 μM), the intracellular Ca +2 chelator BAPTA-AM (5 μM), the mitogen activated protein kinase kinase (MEK) 1/2 and 5 inhibitor U0126 (1 and 10 μM), the p38 mitogen activated protein kinase (MAPK) inhibitor SB203580 (1 μM), the c-Jun amino-terminal kinase (JNK) inhibitor SP600125 (10 μM), and the calcineurin inhibitors FK-506 and cyclosporine A (1.5 and 0.5 μM, respectively). These finding suggest that penitrem A is able to induce an increase in ROS production in neutrophils via the activation of several MAPK-signalling pathways. We suggest that this increase may partly explain the pathophysiology generated by penitrem A neuromycotoxicosis in both humans and animals.